Sociolinguistic Study: The Use of Code Switching, Code Mixing, and Dramaturgical Analysis In a Literary Work - Wellalangi, Maria Beatrix Rahinart (CV. Ridwan Publisher, 2021)
The aims of this study are: (1) to identify types of code switching and code mixing in the novel Prisoner of Your Heart by Irin Sintriana, (2) to identify causal factors of code switching and code mixing in the novel Prisoner of Your Heart, and (3) to illustrate how sociolinguistic concepts apply to the analysis of literature based on the dramaturgical analysis. The research design of this study is descriptive qualitative method. The data are obtained by four techniques of data collections. Based on the data analysis, it can be concluded that there are three types of code switching and code mixing in the novel Prisoner of Your Heart. Those are: (1) inter-sentential switching, (2) intra-sentential mixing, and (3) intra-lexical code mixing. The causal factors of code switching and code mixing in the novel Prisoner of Your Heart are talking about particular topic, to soften or strengthen request or command, and expressing group identity. From the types and causal factors above, the writer makes the correlation of sociolinguistics and literature analysis that literature is not only the effect of social causes but also the cause of social effect. It means that both of literature and sociolinguistics influence each other.